The Silicon-To-Silicon Anodic Bonding Using Sputter Deposited Intermediate Glass Layer - R. Tiwari; S. Chandra (Журнал нано- та електронної фізики)
Glass-to-silicon anodic bonding is an attractive process for packaging of microelectronics devices and Micro-electro-mechanical Systems (MEMS). Silicon to silicon anodic bonding can also be accomplished by incorporating an intermediate glass layer. In the present work, silicon-to-silicon anodic bonding has been studied with an intermediate borosilicate glass layer deposited by RF magnetron sputtering process. The bonding was carried out at low dc voltage of about 48 V at 400 °C. Surface roughness of the deposited intermediate glass film plays a critical role in the success of the bonding process. The surface roughness was observed to be dependent on the thickness of the deposited glass film. It was seen that the surface roughness decreases with increasing thickness of the glass film. The sputter deposited glass layer of 3 µm thickness was found to have very low roughness and this thickness was used as an intermediate layer for silicon-to-silicon bonding process. Alkali ion concentration plays an important role in successful anodic bonding. The concentration of alkali ions was measured by EDX in the sputter deposited film and also in the sputtering target used for preparing the film.